Antibiotic resistance patterns of urinary tract infections in Sanandaj, Iran - Mohsen Rajabnia; Mohammad Bahadoram; Ahmad Fotoohi; Masha Mohammadi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: Urinary tract infection is one of the most common infections. About 10% of people experience it in their lifetime. Due to the significant increase in antibiotic resistance and the unpredictability of antibiotic susceptibility of pathogens, the availability of antibiotic susceptibility testing results can be useful in the selection of the antibiotics based on the type and pattern of antibiotic resistance of the pathogen. Objectives: The aim of this study was to determine the antibiotic resistance pattern of bacteria producing urinary tract infection in Sanandaj, Iran. Materials and Methods: This cross-sectional study was performed on 3126 urinary samples from Tohid hospital in Sanandaj University of medical sciences in 2017. The urine specimens were cultured on EBM (Eosin Methylene Blue) and blood agar media. Kirby-Bauer's standard disk diffusion method was applied to test the susceptibility of the drug for Mueller-Hinton culture agar plates. The results were extracted based on the criteria of CLSL (Clinical and Laboratory Standards Institute). Results: In the study of the samples, the results of 708 cultures (22.64%) were positive. Among the urinary pathogens, Escherichia coli with 291 cases (41/10%) was the most common isolated bacteria. According to the results of antibiogram, the highest antibiotic resistance was observed for cefixime (92.51%), ceftriaxone (52.54%) and cotrimoxazole (45.48%). The highest antibiotic sensitivity was observed for imipenem (96.11%), nitrofurantoin (91.67%) and ceftazidime (88.28%). Conclusion: According to this study, the highest antibiotic resistance was observed with cefixime, ceftriaxone and cotrimoxazole that these drugs are not recommended as the first line of antibiotic therapy. On the other hand, the highest antibiotic susceptibility was observed with Imipenem, nitrofurantoin and ceftazidime, which should be considered in the treatment of urinary tract infections.